Long non-coding RNAs in neurodevelopmental disorders - Van De Vondervoort, Ilse I.; Gordebeke, Peter M.; Khoshab, Nima; Tiesinga, Paul H.; Buitelaar, Jan K.; Kozicz, Tamas; Glennon, Jeffrey C.; Aschrafi, Armaz (Frontiers in Molecular Neuroscience, 2013)
Recent studies have emphasized an important role for long non-coding RNAs (lncRNA) in epigenetic regulation, development, and disease. Despite growing interest in lncRNAs, the mechanisms by which lncRNAs control cellular processes are still elusive. Improved understanding of these mechanisms is critical, because the majority of the mammalian genome is transcribed, in most cases resulting in non-coding RNA products. Recent studies have suggested the involvement of lncRNA in neurobehavioral and neurodevelopmental disorders, highlighting the functional importance of this subclass of brain-enriched RNAs. Impaired expression of lnRNAs has been implicated in several forms of intellectual disability (ID) disorders. However, the role of this family of RNAs in cognitive function is largely unknown. Here we provide an overview of recently identified mechanisms of neuronal development involving lncRNAs, and the consequences of lncRNA deregulation for neurodevelopmental disorders.